Vitamin D deficiency and seasonal variation over the years in São Paulo, Brazil. Issue 12 (December 2016) - Eloi, M.; Horvath, D.; Szejnfeld, V.; Ortega, J.; Rocha, D.; Szejnfeld, J.; Castro, C.
Abstract Summary Brazil is a tropical/subtropical geographic area with elevated ultraviolet (UV) radiation. We report very high prevalence of vitamin D deficiency in a large database of Brazilian subjects and show seasonal and reciprocal relationship between vitamin D and parathyroid hormone (PTH) over the years in this tropical area. Introduction We aim to examine the prevalence of vitamin D deficiency, characterize the temporal relationship between 25-hydroxyvitamin D levels (25(OH)D) and intact PTH (iPTH) according to seasons, and investigate potential associations between 25(OH)D levels and extra-skeletal outcomes in a Brazilian population. Methods We retrospectively determined population weekly mean concentrations of unpaired 25(OH)D and iPTH using 39, 004 laboratory results of Brazilian individuals of both genders aged 2 to 95 years. The 25(OH)D and iPTH distributions were normalized, and the means fit with a sinusoidal function. Potential associations between 25(OH)D serum levels and inflammatory markers, fasting glucose, HbA1c and Homeostasis Model Assessment index (HOMA) were examined. Results Of the samples, 33.9 % had 25(OH)D serum concentrations lower than 20 ng/mL, while the vast majority (70.7 %) were found to be vitamin D deficient or insufficient (<30 ng/mL). Vitamin D deficiency was significantly higher during the winter as compared to the summer (38.4 % <20 ng/mL and 75.5 % <30 ng/mL versus 23.3 % <20 ng/mL and 62.5 % <30 ng/mL, respectively;p  < 0.001). Seasonal variation was observed for both 25(OH)D and iPTH. 25(OH)D peaks occurred in March and troughs in September. iPTH levels showed an inverted pattern of peaks and troughs with a delay of 1 ± 5 week. 25(OH)D was significantly associated with inflammatory markers but not with glucose homeostasis. Conclusions A sinusoidal interrelationship has been detected between vitamin D and PTH in this tropical population. A large percentage of the individuals showed vitamin D deficiency. Public health strategies are needed to better understand and manage this very high and apparently contradictory prevalence of vitamin D deficiency.